1993
DOI: 10.1111/j.1365-2249.1993.tb06493.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher anti-heparan sulphate reactivity during systemic lupus erythematosus (SLE) disease exacerbations with renal manifestations; a long term prospective analysis

Abstract: SUMMARYCross-reactive antibodies against heparan sulphate (HS) have been suggested to play a role in initiating renal disease in SLE. Recently, we found that HS-reactivity is mediated by anti-DNA antibodies complexed with DNA and histones. To evaluate the clinical significance of anti-HS reactivity, we studied prospectively a cohort of 72 consecutive SLE patients, of whom 22 experienced 40 exacerbations. In 20 of these exacerbations renal symptoms were present. In these 20 exacerbations significantly higher an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Concerning other autoantibodies tested such as antiphospholipid antibodies, no association with LN was found thus confirming previous reports as well [21]. Other studies have found that LN patients had significantly higher levels of anti-dsDNA antibodies than patients with no renal disease [23,24]. Anti-dsDNA antibodies may be present in the sera of SLE patients much earlier than previously suspected.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning other autoantibodies tested such as antiphospholipid antibodies, no association with LN was found thus confirming previous reports as well [21]. Other studies have found that LN patients had significantly higher levels of anti-dsDNA antibodies than patients with no renal disease [23,24]. Anti-dsDNA antibodies may be present in the sera of SLE patients much earlier than previously suspected.…”
Section: Discussionsupporting
confidence: 88%
“…41 Cross-sectional and long term prospective studies reported exclusive correlation of the anti-HS reactivity mediated by anti-DNA antibodies with exacerbation of lupus presenting nephritis. 41,42 However, these studies were limited to SLE patients according to the presence or absence of nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…506 [7 9], In some instances, this is attributable to the binding of anti-DNA antibodies to DNA thai is associated with the apparently cross-reactive antigens, leading to in situ immune complex formation [10]. Such indirect reactivity of anti-DNA antibodies towards heparan sulphate has been demonstrated to correlate with exacerbations of lupus nephritis [11].…”
Section: Introductionmentioning
confidence: 99%